2021
DOI: 10.1093/intqhc/mzab031
|View full text |Cite
|
Sign up to set email alerts
|

Hospital nurses’ intention to report near misses, patient safety culture and professional seniority

Abstract: Background Preventable medical errors are the third cause of death after cancer and heart disease. The first step in coping with medical errors in the healthcare system is to develop a culture of patient safety. Reporting medical errors, especially near misses, is one of the chosen methods of dealing with patient safety issues, recommended by the Institute of Medicine. Despite this recommendation, few studies examined the relationship between reporting near misses and improvements in patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 2 publications
6
19
0
Order By: Relevance
“…In addition, the score of barriers to reporting adverse events was significantly and positively correlated with reporting intention; that is, the more the nurses perceived barriers to reporting, the less their reporting intention. Of these, reporting culture had the greatest impact on nurses’ intention to report adverse events, consistent with the findings of Yang et al 56 and Toren et al 57 Previous studies have pointed out that fear of discrimination and punishment is the main reason why nurses do not volunteer to report adverse events. 58 , 59 Similar to Lee et al, 60 we also found that the perceptions of reporting benefits influences nurses’ reporting intentions.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the score of barriers to reporting adverse events was significantly and positively correlated with reporting intention; that is, the more the nurses perceived barriers to reporting, the less their reporting intention. Of these, reporting culture had the greatest impact on nurses’ intention to report adverse events, consistent with the findings of Yang et al 56 and Toren et al 57 Previous studies have pointed out that fear of discrimination and punishment is the main reason why nurses do not volunteer to report adverse events. 58 , 59 Similar to Lee et al, 60 we also found that the perceptions of reporting benefits influences nurses’ reporting intentions.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, safety motivation had no direct effect on patient safety event reporting, which again represents a significant difference from previous studies that posited the influence of safety motivation on safety behavior [19,39]. For example, Toren et al stated that most nurses (80%) demonstrated an intention to report medical errors and near misses, although 53% of them had not reported near misses in the past year [52]. Thus, there was a difference found between participants' reported intentions and their actual near-miss reporting.…”
Section: Discussionmentioning
confidence: 75%
“…ror reporting was contingent upon the severity of the consequences to the patients; they would not instead report near-miss cases or errors without consequences, even informally. Toren et al reported a discrepancy between what nurses describe as their intent to report a near-miss event and their actual reporting of an event (35). Nurses fear intimidation, retribution, or punitive measures.…”
Section: Conflict Of Interestsmentioning
confidence: 99%